Understanding the Role of Generative Pre-Trained Transformer (GPT) in Improving Learning Quality and Practices - Fahry Rizaldy Putra; Dyah Setyowati Ciptaningrum (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
Generative Pre-trained Transformers (GPTs) are an artificial intelligence model gaining popularity in educational technology development. GPTs are models that are massively trained on diverse texts and can generate texts with structure and meaning. The utilization of GPT in education offers great potential to improve the quality of learning, both inside and outside the classroom. This study aims to understand the role of GPT in improving the quality and practice of learning. This research uses a qualitative research method with a case study method. Data collection techniques in this research include literature study, interviews, and observation. Thematic analysis will be used as the main data analysis technique. The results show that GPT has the potential to be a supportive and interactive tool to increase student motivation in the learning process. The participants perceived GPT as a convenient and efficient means to access information, complete assignments, and receive personalized content tailored to their interests and learning styles.